2018
DOI: 10.1002/ange.201712286
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Modulation of Structural Polymorphism in Pathogenic α‐Synuclein Fibrils Using Copper(II) Coordination

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…A similar relationship between tau compaction and charge state was also observed for the singly CLR0l-bound C291A 4R-tau fragment, especially for the lower charge states (Figure S6). The TWIMS resolving power for these tau proteins is similar to our TWIMS measurements of another intrinsically disordered protein, α-synuclein [47, 51] and a recent TWIMS study of tau proteins [52]. …”
Section: Resultssupporting
confidence: 78%
“…A similar relationship between tau compaction and charge state was also observed for the singly CLR0l-bound C291A 4R-tau fragment, especially for the lower charge states (Figure S6). The TWIMS resolving power for these tau proteins is similar to our TWIMS measurements of another intrinsically disordered protein, α-synuclein [47, 51] and a recent TWIMS study of tau proteins [52]. …”
Section: Resultssupporting
confidence: 78%
“…In terms of the amyloid potential of the protein, as mentioned above, no significant differences were observed in the fibrillation kinetics between acetylated and non‐acetylated AS, whereas the fibrillation enhancement observed for AS at an equimolar Cu(II) stoichiometry did not occur with the acetylated variant of the protein (Moriarty et al, ). Indeed, a recent study showed that the conformation of the non‐acetylated AS monomer would be strained by macrochelation with Cu(II) at sites 1 and 2, thereby disrupting fibril elongation and promoting amyloid nucleation (Choi et al ). According to this study, this interaction leads to the formation of shortened, β‐sheet enriched fibrils (< 0.2 μM) that are rapidly transmitted and accumulated to neuronal cells, causing neuronal cell death, in sharp contrast to typical AS fibrils (ca 1 μM).…”
Section: Linking Post‐translational Modifications and Metal‐binding Imentioning
confidence: 99%
“…These shortened fibrils exhibit rapid transmission and accumulation in neuronal cells, ultimately resulting in neuronal cell death. This is in stark contrast to typical αSyn fibrils, which are larger in size (approximately 1 μm) [ 38 ]. TETA (triethylenetetramine) has been demonstrated to mitigate the harmful impact of copper ions on the toxic spread of αSyn fibrils.…”
Section: Factors Influencing Protein Aggregationmentioning
confidence: 93%
“…H50 is situated within the β-sheet-aligned core region of αSyn, and the conformation of the αSyn-Cu 2+ complex is constrained specifically within residues 1–50. As a result, the structural reorientation of residues 1–50, which is necessary for the assembly onto the αSyn nucleus, is altered [ 38 ]. This is further supported by evidence that H50 in mature fibrils cannot coordinate copper [ 39 ].…”
Section: Factors Influencing Protein Aggregationmentioning
confidence: 99%